Experimental Assessment of the Impact of Sonication Parameters on Necrotic Lesions Induced in Tissues by HIFU Ablative Device for Preclinical Studies - FURA, Łukasz; DERA, Wojciech; DZIEKOŃSKI, Cezary; ŚWIĄTKIEWICZ, Maciej; KUJAWSKA, Tamara (Archives of Acoustics, 2021)
We have designed and built ultrasound imaging-guided HIFU ablative device for preclinical studies on small animals. Before this device is used to treat animals, ex vivo tissue studies were necessary to determine the location and extent of necrotic lesions created inside tissue samples by HIFU beams depending on their acoustic properties. This will allow to plan the beam movement trajectory and the distance and time intervals between exposures leading to necrosis covering the entire treated volume without damaging the surrounding tissues. This is crucial for therapy safety. The objective of this study was to assess the impact of sonication parameters on the size of necrotic lesions formed by HIFU beams generated by 64-mm bowl-shaped transducer used, operating at 1.08 MHz or 3.21 MHz. Multiple necrotic lesions were created in pork loin samples at 12.6-mm depth below tissue surface during 3-s exposure to HIFU beams with fixed duty-cycle and varied pulse-duration or fixed pulse-duration and varied duty-cycle, propagated in two-layer media: water-tissue. After exposures, the necrotic lesions were visualized using magnetic resonance imaging and optical imaging (photos) after sectioning the samples. Quantitative analysis of the obtained results allowed to select the optimal sonication and beam movement parameters to support planning of effective therapy.